2004
DOI: 10.1074/jbc.m409284200
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Studies of the Afa/Dr Adhesin DraE and Its Interaction with Chloramphenicol

Abstract: Pathogenic Escherichia coli expressing Afa/Dr adhesins are able to cause both urinary tract and diarrheal infections. The Afa/Dr adhesins confer adherence to epithelial cells via interactions with the human complement regulating protein, decay accelerating factor (DAF or CD55). Two of the Afa/Dr adhesions, AfaE-III and DraE, differ from each other by only three residues but are reported to have several different properties. One such difference is disruption of the interaction between DraE and CD55 by chloramph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 41 publications
6
88
1
Order By: Relevance
“…The b-sheet and turns/unordered components accounted for about 84 % and 16 % of the amide I band area, respectively. These FTIR data are in agreement with published structures of AfaE-dsc and DraE proteins Pettigrew et al, 2004). The IR data presented showed that the insertion of the heterogenic epitopes into the A2-B loop of the DraE subunit did not perturb the Ig-barrel structure of the adhesin to any detectable extent.…”
Section: Ir Spectroscopy Of Native and Chimeric Fimbriaesupporting
confidence: 81%
“…The b-sheet and turns/unordered components accounted for about 84 % and 16 % of the amide I band area, respectively. These FTIR data are in agreement with published structures of AfaE-dsc and DraE proteins Pettigrew et al, 2004). The IR data presented showed that the insertion of the heterogenic epitopes into the A2-B loop of the DraE subunit did not perturb the Ig-barrel structure of the adhesin to any detectable extent.…”
Section: Ir Spectroscopy Of Native and Chimeric Fimbriaesupporting
confidence: 81%
“…These adhesins are assembled via the chaperone-usher pathway (260,520). The DraE adhesin subunit expresses two separate adhesion domains; the first recognizes the human decay-accelerating factor (hDAF) at the complement control protein (CCP) 2 and 3 domains (521)(522)(523)(524), and the second recognizes the N domains of several hCEACAMs (525)(526)(527)(528)(529). The physiological role of hDAF is to inhibit the complement cascade at the level of the critical C3 convertase step for the protection of normal cells from complement-mediated attack during innate activation, and in addition hDAF serves as a receptor for certain strains of pathogenic E. coli, Helicobacter pylori, and certain types of enteroviruses (530).…”
Section: Cell Interaction Cell Entry and Intracellular Lifestylementioning
confidence: 99%
“…Structure-function analysis of Dr adhesin has been performed using various different mutants (11,30,32,44,45,61). One of them, the mutant strain Dr ϩ D54C (in which aspartic acid 54 is replaced by cysteine), retains hDAF-binding capability (11) but has lost the ability to mobilize hDAF around adhering Drpositive bacteria (23).…”
Section: Mutation At Aspartic Acid 54 On the Drae Adhesin Subunit Abomentioning
confidence: 99%
“…The DraE adhesin subunit has a distinct hCEACAM member binding site located primarily in its A, B, E, and D strands, located opposite the beta sheet encompassing the binding site for hDAF, indicating that the adhesin subunit can bind simultaneously to both receptors on the epithelial cell surface (31). Conformational receptor-binding studies have been conducted in order to identify the amino acid sequences in the major structural DraE and DaaE adhesin subunits engaged in receptor recognition (11,30,44,45,62).…”
mentioning
confidence: 99%